2018
DOI: 10.7717/peerj.4398
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of glucocorticoid hormones in vertebrates: a meta-analysis

Abstract: We often expect that investigations of the patterns, causes, and consequences of among-individual variation in a trait of interest will reveal how selective pressures or ecological conditions influence that trait. However, many endocrine traits, such as concentrations of glucocorticoid (GC) hormones, exhibit adaptive plasticity and, therefore, do not necessarily respond to these pressures as predicted by among-individual phenotypic correlations. To improve our interpretations of among-individual variation in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 66 publications
8
37
1
Order By: Relevance
“…Further, stress-induced but not baseline levels were positively correlated with female and male barn owl survival. The lack of viability selection on baseline corticosterone levels may be due to reduced statistical power or to the high sensitivity of baseline corticosterone levels to several environmental factors or life history stages (Angelier et al, 2009;Cockrem et al, 2009;Hennessy et al, 2015;Rensel & Schoech, 2011;Schoenemann & Bonier, 2018). Overall, our results suggest that corticosterone levels in the barn owl are under positive directional selection (if at all).…”
Section: Con Clus Ionmentioning
confidence: 76%
“…Further, stress-induced but not baseline levels were positively correlated with female and male barn owl survival. The lack of viability selection on baseline corticosterone levels may be due to reduced statistical power or to the high sensitivity of baseline corticosterone levels to several environmental factors or life history stages (Angelier et al, 2009;Cockrem et al, 2009;Hennessy et al, 2015;Rensel & Schoech, 2011;Schoenemann & Bonier, 2018). Overall, our results suggest that corticosterone levels in the barn owl are under positive directional selection (if at all).…”
Section: Con Clus Ionmentioning
confidence: 76%
“…However, our results do not allow us to know whether these differences in the physiological responses of urban and rural individuals are plastic responses toward differences in the degree of human perturbation or result from a non-random distribution of individuals showing fixed, unchanging, physiological profiles. Although some studies on this topic have been conducted ( Schoenemann and Bonier, 2018 ; Taff et al , 2018 ), there is no agreement regarding how much of the stress-induced response of individuals remains constant throughout their lives and how much corresponds to individual responsiveness to environmental variation. This information is paramount to understanding the mechanisms underlying the differences observed between urban and rural individuals, as natural selection and matching habitat choice rely on the assumption that the traits of interest remain constant through an individual’s lifespan and are heritable, while habituation (phenotypic plasticity) assumes that organisms are able to respond to variation in the environment by modifying their phenotype (although there are studies showing that plasticity per se can also be heritable and genetically fixed; Hallsson and Björklund, 2012 ; Scheiner et al , 2012 ; Gomez-Mestre and Jovani, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ICC of 0.19 also indicates that there is little tendency for measurements within the same marmot to be similar, meaning that there is low repeatability of GC measurements in this population. In a recent meta-analysis, Schoenemann and Bonier (2018) found that the mean repeatability of GC measurements in other vertebrates (when measured using substrates such as hair and feathers) was 0.32, with a 95% confidence interval of 0.24–0.41. Thus, our results suggest below average repeatability.…”
Section: Discussionmentioning
confidence: 99%